Effect of cooking on the antioxidant activity of taro (Colocasia Esculenta cv. Itchina) - Lu, Jamie Chris Herrera
ABSTRACT This study aimed to evaluate the effect of steaming (10 min), boiling (10, 20 and 30 min) and poi processing, on the total phenolic content and antioxidant activity of the taro tuber. Methanolic extracts of freeze-dried samples were tested for total phenolic, through the Folin-Ciocalteau assay, while antioxidant activities were measured through DPPH free-radical scavenging ability, reducing power, ferrous ion-chelating capacity and inhibition of linoleic acid peroxidation. Total phenolic content ranged between 13.62 to 26.44 mg gallic acid equivalents/100 g dry matter and correlated well with reducing power and DPPH free radical scavenging ability. The cooking treatments had a significant effect on the total phenolic content, DPPH free radical scavenging ability and reducing power, but none on ferrous ion-chelating ability. Steaming, in general, preserved more of the phenolic content and antioxidant activities, while poi processing had the most detrimental effect. Losses from the cooking methods have been attributed to heat degradation, oxidation, leaching of antioxidant compounds in the cooking water. Antioxidant activity (AOX) expressed as inhibition of linoleic acid peroxidation showed the order of steamed (10 min)>boiled (10 min)>boiled (20 min)>poi>boiled (30 min). A negative and high correlation was observed between AOX and heating time (R=-0.95) regardless of the cooking method used. Antioxidant activity correlated well only with DPPH radical scavenging ability indicating that total phenolic content may be a minor contributor to the antioxidant activity of taro. Findings show that the taro flesh can be a good dietary source of phenolics and natural antioxidants. To preserve more of these compounds with cooking, shorter heating times are recommended.